691 Associations of Sleep Quality and Burnout in Clinicians during the COVID-19 Pandemic. (3rd May 2021) - Shechter, Ari; Rosenfeld, Adam; Chang, Bernard; Norful, Allison
Abstract: Introduction: Clinicians have faced unprecedented challenges in care delivery during the COVID-19 pandemic due to increases in patient volume/acuity, alongside fears of COVID-19 exposure. Increased burnout rates are associated with chronic health condition risk and adverse organizational outcomes. It remains unclear whether sleep is associated to burnout in clinicians treating COVID-19 patients. Methods: A cross-sectional electronic survey was distributed via email across 3 hospital listserves from September to November, 2020. Clinicians delivering direct care to COVID-19 patients were eligible. Clinician burnout was measured using a single item from AHRQ's Mini-Z survey. We assessed sleep using the Pittsburgh Sleep Quality Index (PSQI). Binary logistic regressions were used to determine the relationship between PSQI global score (global sleep quality) and burnout, controlling for age, race/ethnicity, gender, length of time employed, whether clinical role changed during COVID-19, and anxiety. In a separate model, we investigated the association between burnout and independent PSQI subcomponents: 1) sleep duration ("Hours of sleep per night"), and 2) subjective sleep quality ("How would you rate your sleep quality overall") entered together, with the above covariates. Results: The final sample included 315 clinicians, predominantly nurses (57% White, 15% Hispanic/Latino, 89% female). Burnout symptoms were reported by 61.6%, and poor global sleep quality (PSQI global score >5) in 84.4% of participants. Poor global sleep quality (PSQI global score >5 vs. ≤5) was significantly associated with the presence of burnout symptoms (OR: 2.52, 95% CI: 1.20–5.28, p=0.015). In the secondary model, self-reported sleep quality (rating of fairly or very bad vs. rating of fairly or very good) was significantly associated with burnout (OR: 4.13, 95% CI: 2.33–7.32, p<0.05), whereas short sleep duration (<6 h vs. ≥6 h) was not (OR: 0.726, 95% CI: 0.41–1.30, p=0.28). Conclusion: Poor sleep quality is common and associated with increased burnout in clinicians delivering care to COVID-19 patients. Interestingly, sleep quality appears to be more strongly related to burnout than sleep duration. Increased evidence about the negative implications of poor sleep and burnout are emerging. Interdisciplinary efforts aimed at promoting effective sleep quality in clinicians during this pandemic may lead to improvements in long-term clinician physical and psychological health. Support (if any):